2018
DOI: 10.7150/jca.23280
|View full text |Cite
|
Sign up to set email alerts
|

Interventional radiofrequency ablation: A promising therapeutic modality in the management of malignant biliary and pancreatic duct obstruction

Abstract: Background: Malignant biliary and/or pancreatic obstruction has often encountered in the advanced stages of periampullary and cholangicarcinomas. HabibTM Radiofrequency (RF) ablation has been successfully used in the management of various cancers of liver and pancreas. Percutaneous HPB probe (EMcision Ltd, London, UK) is a new addition to this class of tools. It is an endoluminal Radiofrequency (RF) catheter which works on the principle of ablation and induces coagulative necrosis to recanalize the obstructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Monga confirmed the disappearance of tumour blood vessels and lumen enlargement after intra-RFA [ 25 ]. Several studies have reported the clinical efficacy, safety, and survival benefit of intra-RFA for MBO [ 13 , 15 , 26 ]. In a prospective, randomised trial comparing intra-RFA + stent placement with stent placement alone for unresectable extrahepatic cholangiocarcinoma with BO, the combined treatment significantly improved the overall mean survival time and mean stent patency period (6.8 vs. 3.4 months; p = 0.02; 13.2 ± 0.6 vs. 8.3 ± 0.5 months; p < 0.001) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monga confirmed the disappearance of tumour blood vessels and lumen enlargement after intra-RFA [ 25 ]. Several studies have reported the clinical efficacy, safety, and survival benefit of intra-RFA for MBO [ 13 , 15 , 26 ]. In a prospective, randomised trial comparing intra-RFA + stent placement with stent placement alone for unresectable extrahepatic cholangiocarcinoma with BO, the combined treatment significantly improved the overall mean survival time and mean stent patency period (6.8 vs. 3.4 months; p = 0.02; 13.2 ± 0.6 vs. 8.3 ± 0.5 months; p < 0.001) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor size remained stable in 55.6% (10/18) of patients at 1 month of follow up abdominal CT scan, and increased in 44.4% (8/18) patients which raised question about the effectiveness of percutaneous RFA ( 30 ). Mizandari et al performed percutaneous intraluminal RFA coupled with stent placement was used in 134 patients with malignant obstructions of bile and pancreatic ducts (32 patients with pancreatic adenocarcinoma) and reported a 97% success rate of procedure with only two patients experienced procedural technique related adverse events (contrast extravasation) following RFA ( 36 ).…”
Section: Percutaneous Radiofrequency Ablationmentioning
confidence: 99%
“…RFA with subsequent stent placement has been successfully used to re-canalize biliary or pancreatic ducts that were obstructed by unresectable tumors ( 36 ). Indeed, ductal decompression with stenting is considered standard of care in patients with malignant obstruction of biliary or pancreatic ducts due to unresectable tumors, however, stents are often prone to occlusion ( 23 , 24 , 48 – 50 ).…”
Section: Endoscopic-guided Radiofrequency Ablationmentioning
confidence: 99%
“…Endoscopic drainage has a low risk of complications, but it is associated with a high probability of recurrent biliary obstruction [32] when compared with surgical bypass. After an endobiliary radiofrequency ablation (RFA) system was applied to biliary malignant obstructions, series intra-luminal RFA and self-expanding metal stents (SEMS) became a safe treatment choice with better intervention-free survival compared to SEMS alone [33][34][35]. Percutaneous trans-hepatic cholangiography and drainage (PTCD) should be reserved for unsuccessful endoscopic procedures in patients with MDBO.…”
Section: Malignant Distal Biliary Obstructionmentioning
confidence: 99%